2-Hydroxy-16-[(E)-4-hydroxy-3-methoxybenzylidene]-13-(4-hydroxy-3-methoxyphenyl)-11-methyl-1,11-diazapentacyclo[12.3.1.0(2,10).0(3,8).0(10,14)]octadeca-3(8),4,6-triene-9,15-dione - Kumar, Raju Suresh (International Union of Crystallography, 2010)
In the title compound, C(32)H(30)N(2)O(7), the piperidone ring adopts a chair conformation and the five-membered ring of the dihydroindenone ring system adopts an envelope conformation. Intramolecular O—H⋯N and C—H⋯O hydrogen bonds occur. The dihedral angle between the two hydroxy-subsituted methoxyphenyl rings is 71.12 (5)°. In the crystal structure, molecules are connected by intermolecular O—H⋯O hydrogen bonds, forming layers parallel to (001). These layers are further connected by C—H⋯O hydrogen bonds, forming a three-dimensional network.